Krause, Grandmothers, Mothers, And Daughters- Oral History Of Three Generations Of Ethnic American Women - Brown, Terry (Teaching History: A Journal of Methods, 1993)
This work is based on a study of 225 women conducted in the mid-1970s, entitled "Women, Ethnicity, and Mental Health." Follow-up interviews in the late 1980s with eighteen of the women updated their reactions. Italian, Jewish, and Slavic immigrants made up the principal ethnic groups in Pittsburgh in 1900 and are the focus of this survey. Changes in peasant economies and religious pogroms drove thousands of families from eastern and southeastern Europe to seek better opportunities in the United States.